Phi Shape UWB Antenna with Band Notch Characteristics - Ajetrao, K. V.; Dhande, A. P. (Engineering, Technology & Applied Science Research, 2018)
In this paper a novel band notch antenna in UWB frequency range is designed using split rings. Split rings are overlapped with designed monopole to give phi shape. The slit gap gives band-notch operation from 5.1GHz to 6.29GHz and from 4.94GHz to 5.91GHz for SPSSR and SPSCR antennas respectively. Simulated and measured results are in good agreement.